Temperate forest termites: ecology, biogeography, and ecosystem impacts - M A Y N A R D, D A N I E L; C R O W T H E R, T H O M A S W .; K I N G, O S H U A R; W A R R E N, R O B E R T J .; B R A D F O R D, M A R K A . (published online, 2015)
Wood decomposition in temperate forests is dominated by termites, fungi, and some species of ants and beetles. Outside of urban areas, temperate termite ecology is largely unknown, particularly when compared to tropical termites and other temperate organisms in the functional guild of wood-decomposing animals. 2. This review combines climate habitat modelling with knowledge of species physiology, behaviour, and community interactions to identify and prioritise future research on temperate termite ecology and biogeography. 3. Using a correlative climate model, the regional distributions of three common temperate forest termite species are shown to correlate with different aspects of climate (e.g. mean versus minimum monthly temperature), but that overall their distributions within temperate systems correlate more strongly with temperature variables than with precipitation variables. 4. Existing data are synthesised to outline how the subterranean, wood-nesting behaviour of most temperate forest termite species links their activity to an additional set of non-climate controls: wood type and tree species, soil depth, fungal activity, ant abundances and phenology, and competitive asymmetries among termite species. 5. Although fine-scale estimates of temperate termite abundances are rare, we provide upper bounds on their ecosystem impacts and illustrate how their regional abundances may influence forest structure and habitat availability for other organisms. 6. This review highlights that rigorous ecological studies in non-urban, intact ecosystems – with a particular focus on community interactions – are critically needed to accurately project future abundances, economic impacts, and ecosystem effects of temperate forest termites.
full text
Keywords: Biogeography, carbon cycling, Coptotermes, decomposition, fungi, Maxent, Reticulitermes, review, soil biodiversity, species distribution modeling